PERAN GURU IPS TERPADU DALAM PEMBENTUKAN KARAKTER SISWA DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 05 TEMPUNAK TAHUN PELAJARAN 2018/2019 - Yulia Suriyanti; Yunita Astikawati (JURKAMI : Jurnal Pendidikan Ekonomi, 2021)
Behavioral deviations that are often carried out by students in the school environment both in the learning process and outside the learning process. This study is to find out how the character of students, the role of Integrated Social Studies teachers, and supporting and inhibiting factors in forming student character. This research is a descriptive qualitative study, subjects of Integrated Social Studies teachers, Principals and 6 students. Instrument for observation, interview and documentation research. The results showed that the Role of  Integrated Social Studies Teacher in Character building Students in State Junior High School 05 Tempunak 2018/2019 School Year includes instructors, mentors, educators, demonstrators, evaluators, motivators, advisors, role models, mediators and facilitators, trainers, individuals, workers routine, actor, and preservative. While the characters formed in students are diligent, honest, resilient/persistent, trustworthy, responsible, hard-working, willing to work together, and be polite, lazy, likes to lie, likes to cheat, want to win alone/selfish, said harshly and like to bully friends.